Comprehension of complex syntax by non-English-speaking children with developmental language disorder: A scoping review - Georgiou, Georgios P.; Theodorou, Elena (My University, 2022)
Children with developmental language disorder (DLD) are characterised by impaired language abilities both in comprehension and production. Complex syntax is a specific domain which is often considered challenging for children with DLD. Research regarding complex syntax is mostly concerned with the production patterns of speakers and usually employs English-speaking populations. This scoping review aims to systematically map the abilities of non-English-speaking children with DLD to comprehend complex syntactic structures, comparing these results with the broader literature on English-speaking children with DLD. It also aims to consider the account (i.e. grammatical vs processing) by which these abilities can be explained. Four online databases were used to extract original research articles published between 2011 and 2021. Of the 264 studies initially identified, 20 studies were included in the review. The results demonstrated that children with DLD present with difficulties in comprehending object relative clauses, wh-questions, sentences with non-canonical word order, passives, and other types of complex syntax. All of these challenges are also evident in English-speaking children with DLD and can be mainly attributed either to the inability of children to assign thematic roles, their restricted working memory capacities, or a combination thereof. It is concluded that the comprehension of complex syntax might be a universal marker of DLD, which can be explained on the basis of either a grammatical or a processing account, or both. Common challenges in certain structures across languages can be used to design a comprehension assessment tool that can be applied in several languages.
Keywords: Scoping review; Children; Complex syntax; Comprehension; Language developmental disorder